STUDI EFEKTIVITAS PEMBERIAN PUPUK SILIKA (Si) TERHADAP PERTUMBUHAN, PRODUKSI DAN KUALITAS TANAMAN CABAI (Capsicum annum L.) DI ERA NEW NORMAL - Nur Fitriyah; Muhamad Arif Prayogo (BUANA SAINS, 2021)
Red chili pepper ( Capsicum annum L.) was a commodity whose inconsistent supply availability and short storage period. During pandemic covid 19 and PSBB (Large-Scale Social Restrictions), a horticultural commodity must be pursued to have high growth, production, long storage period, and maintain physical and nutritional qualities during distribution. The research aimed to increase chili pepper growth, productivity, and quality with silica fertilizer treatment. The treatments in this experiment were addition silica with concentrations 0% (control), 25% silica, 50 %, and 75% . The results showed that the addition of silica fertilizer (Si) increased the vegetative growth of Chili Pepper plants. Silica fertilization (Si) with a concentration of 50% increased vegetative growth and storage period of chili pepper but did not increase the fruit size and weight of chili pepper.